2019
DOI: 10.1002/pa.2021
|View full text |Cite
|
Sign up to set email alerts
|

Employee engagement and task performance in state‐owned enterprises in developing countries: The case study of the power sector in Ghana

Abstract: A growing number of studies prove a relationship between employee engagement (EE) and performance. Unfortunately, almost all originate in the developed world; the few that look at developing countries, including their public sectors, have focused more on the civil service and agencies, and neglect state‐owned enterprises (SOEs), despite their importance for delivery of public services. The purpose of this paper is to examine the impact of EE on task performance in SOEs in developing countries, with particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…In the Ghanaian context, Ashley (2018) investigated the association between employee engagement and organizational commitment within the banking sector. Ohemeng et al (2020) also investigated employee engagement and its association with task performance. However, studies about employee engagement and supervisory support are lacking in the Ghanaian context.…”
Section: Introductionmentioning
confidence: 99%
“…In the Ghanaian context, Ashley (2018) investigated the association between employee engagement and organizational commitment within the banking sector. Ohemeng et al (2020) also investigated employee engagement and its association with task performance. However, studies about employee engagement and supervisory support are lacking in the Ghanaian context.…”
Section: Introductionmentioning
confidence: 99%
“…2.4 Hypotheses development 2.4.1 Employee engagement and employee performance. Several studies conducted on EE have established that there is a positive relationship between the term and employee performance which also leads to increased organizational outcomes (Amoako-Asiedu and Obuobisa-Darko, 2017; Govender and Bussin, 2020;Ohemeng et al, 2020;Tensay and Singh, 2020;Satata, 2021;Linggiallo et al, 2021) and that the quality of individual performance in an organization is determined by the level of EE (Satata, 2021). These studies were conducted in different settings and may not be generalized to infer from the evidence above.…”
Section: Employee Performancementioning
confidence: 99%
“…Particularly, Anitha (2014) incorporated a study on 383 employees from Coimbatore city and demonstrated a significant influence of employee engagement on task performance. Task performance of an individual depends upon how much emotionally, cognitively and physically hihe/sher is engaged with hihe/sher job because the level of engagement motivates employees to perform well (Pattnaik and Sahoo, 2020;Ohemeng et al, 2020;Bhardwaj and Kalia, 2021). Hence, keeping in mind the abovementioned studies, following hypothesis has been formulated:…”
Section: Employee Engagement and Task Performancementioning
confidence: 99%
“…Task performance is the combination of outcomes of exerting efforts (Borman and Motowidlo, 1993). One’s cognitive, emotional and physical attachment towards assigned job as well as organization encourages one for being diligent to achieve desired results; such degree of attachment elevates task performance of employees (Pattnaik and Sahoo, 2020; Ohemeng et al, 2020). Task performance is identified as a result-oriented behavioural phenomenon that is an outcome of employee engagement (Shantz et al, 2013; Anitha, 2014).…”
Section: Introductionmentioning
confidence: 99%